Mutant NDUFS3 subunit of mitochondrial complex I causes Leigh syndrome. Issue 1 (16th January 2004) - Bénit, P; Slama, A; Cartault, F; Giurgea, I; Chretien, D; Lebon, S; Marsac, C; Munnich, A; Rötig, A; Rustin, P
Abstract : Respiratory chain complex I deficiency represents a genetically heterogeneous group of diseases resulting from mutations in mitochondrial or nuclear genes. Mutations have been reported in 13 of the 14 subunits encoding the core of complex I (seven mitochondrial and six nuclear genes) and these result in Leigh or Leigh-like syndromes or cardiomyopathy. In this study, a combination of denaturing high performance liquid chromatography and sequence analysis was used to study the NDUFS3 gene in a series of complex I deficient patients. Mutations found in this gene (NADH dehydrogenase iron-sulphur protein 3), coding for the seventh and last subunit of complex I core, were shown to cause late onset Leigh syndrome, optic atrophy, and complex I deficiency. A biochemical diagnosis of complex I deficiency on cultured amniocytes from a later pregnancy was confirmed through the identification of disease causing NDUFS3 mutations in these cells. While mutations in the NDUFS3 gene thus result in Leigh syndrome, a dissimilar clinical phenotype is observed in mutations in the NDUFV2 and NDUFS2 genes, resulting in encephalomyopathy and cardiomyopathy. The reasons for these differences are uncertain.